Medical Information on Optical Disc - Schipma, Peter B. (1987)
Optical discs may permit a revolutionary change in the distribution and use of medical information. A single compact disc, similar in size to that used for digital audio recording, can contain over 500 million characters of information that is accessible by a Personal Computer. These discs can be manufactured at a cost lower than that of print on paper, at reasonable volumes. Software can provide the health care professional with nearly instantaneous access to the information. Thus, for the first time, the opportunity exists to have large local medical information collections. This paper describes an application of this technology in the field of Oncology.